Women owners of small or medium companies and their stakeholder relationship in Nottingham: an exploratory research - Garcia-Hjarles Villanueva, Galia Rocio (2009)
In Europe, for the last twenty years, small and medium enterprises (SMEs) have become an important engine of the economy (Jenkins, 2004). SMEs are no longer left as outsiders’ organizations and their impacts in society as a group can be enormous. Now they are spaces for innovation, creativity, employment, job opportunities and efficiency (Spence and Rutherfoord, 2003). On the other hand, the SMEs community is very heterogeneous, and their performance is influenced by different factors such as size, sector, financial resources, owner gender, and stakeholders.